CS 240B - Microsoft Windows Server Admin II - Ziko Rizk (Linn-Benton Community College, 2019)
This is the second of two courses in the administration of Microsoft Windows® client/server networked operating systems. The courses CS 240A and CS 240B are laboratory-intensive courses that provide hands-on experience in the planning, installation, and administration of Microsoft Windows® client/server networks. The two courses provide partial preparation for the MCSA® and MCSE® exams.